Investigation of in Vitro Wound Healing Activity of Polygonatum orientale Desf. Rhizome - Ghazal Hashemi; Hamid-Reza Adhami; Mahban Rahimifard; Maryam Baeeri; Parisa Sarkhail (Tehran University of Medical Sciences, 2022)
In this study, we carried out a bioassay-guided fractionation of the most active extract Polygonatum orientale Desf. rhizome, in order to isolate and identify the fraction/s or compound/s responsible for wound healing activity. The wound healing process considered via scratch wound assay on NIH-3T3 fibroblasts. The results showed that the methanol extract and its fractions A5 and A6 showed excellent wound healing effect and were rich of bioactive glycoside compounds. Fraction A6 was selected for further fractionation and two sub-fractions B5 and B6 showed acceptable wound healing on fibroblasts. B5-P (sucrose) and B6-P were isolated as two active compounds from theses fractions that significantly reduced wound area, without any toxicity at very low concentrations (50-200 ng/mL). These results supported the traditional use of P. orientale rhizome for wounds treatment and showed that the accelerated wound healing activity of the rhizome is due to the presence of bioactive polar compounds.